LEVERAGING DIGITAL SOLUTIONS FOR NEW ENERGY SYSTEMS MODELLING AND OPTIMISATION - Angela Solano; Arash Behrang; Juan Montelongo; Raul Cota; Victor Manuel Rodriguez De Vecchis; Valentina Gonzalez Perez (Proceedings on Engineering Sciences, 2025)
The paper addresses the limitations of traditional segmented approaches in modeling and optimizing energy systems, particularly in geothermal energy and carbon capture and sequestration (CCS). Historically, these systems were analyzed in isolation, with separate tools for subsurface and surface simulations, leading to inefficiencies and potential errors due to manual data transfer and inconsistencies between thermodynamic models. To overcome these challenges, the paper introduces an integrated "pore-to-process" workflow, which unifies reservoir simulation with process simulation platforms into a single, cohesive framework. This workflow enhances the accuracy and efficiency of system modeling by ensuring consistent thermodynamic calculations across both subsurface and surface components. By automating data transfer and reducing manual input, the workflow minimizes errors and computational overhead, allowing for real-time data sharing and holistic system optimization. The paper demonstrates the effectiveness of this approach in geothermal energy systems, where it improves efficiency by integrating subsurface dynamics with surface facility performance.